Reliability of Palaeozoic palaeomagnetic poles and APWP of Gondwanaland - Schmidt, P. W.; Powell, C. Mc A; Li, Z. X.; Thrupp, G. A. (Tectonophysics, 1990)
A review of reliable palaeomagnetic data from Gondwana Palaeozoic rocks supports the apparent polar wander path (APWP) initially proposed by Morel and Irving. This path, or versions of it, has recently gained favour with a number of groups. The APWP suggests that during the mid-Palaeozoic Gondwanaland was very mobile. No palaeomagnetic pole position(s) has been yet reported that confirms the contentious segment of APWP from the Late Ordovician to the Early Silurian. The APWP implies that the south pole moved rapidly from north Africa in the Ordovician to a position off southern South America by the Silurian, back to central Africa by the Early Carboniferous and across Gondwanaland to Australia by the Late Carboniferous. The distribution of Palaeozoic tillites independently supports such a mobilistic Gondwanaland. The palaeomagnetic and tectonic evidence are compatible with the Lachlan Fold Belt of Australia having been in place since the mid-Devonian.